Urban Mission Strategy Through One-on-One Online Dialogue in Melbourne Australia - Yanto Paulus Hermanto; Petrus Antonius Usmanij; Sonny Eli Zaluchu (Jurnal Jaffray, 2023)
This paper reports the results of research on urban evangelism conducted online using a Zoom application with one-on-one techniques. The method is to conduct worldview talks with other religions in Melbourne, Australia. The dialogue refers to three key questions: (1) What is the worldview of your belief or religion? (2)  Is there more to life than this? and (3) How does your belief or religion contribute to your life? The paper is presented in the form of descriptive reports. As a result, dialogue between religious people through a worldview approach in urban areas is effective as an effort to deepen the beliefs of others and introduce religious teachings embraced by other religions. The research contributes to the strategy of contemporary urban missions in the pandemic in the digital community. It provides new insights that evangelism can be done using technological devices in addition to the traditional way.